Arthropod diversity and abundance in rose flowers at Shadullapur, Savar, Dhaka, Bangladesh - Rimu Islam Tuly; Mohammad Abdur Razzak (Arthropods)
Arthropod species pose a significant threat to ornamental plants through feeding, ovipositional injury, and the spread of pathogenic microbes.This study investigated arthropod species infesting rose plants grown at Shadullapur, Savar, Dhaka, Bangladesh, from October 2019 to February 2020. A total of 1,454 individuals from seven insect orders and two arachnid groups were recorded. Individuals from the order Thysanoptera were the most abundant, followed by Hemiptera and Lepidoptera. Among arachnids, spider mites and predatory mites were dominant. A total of 25 species were identified, including 22 insect species and three arachnids. Lepidoptera exhibited the highest species diversity, followed by Hemiptera and Coleoptera. The Shannon Diversity Index of 0.9596 indicates a moderate level of species diversity, suggesting that while a few orders dominate in abundance, a variety of species contribute to the ecosystem.This study highlights the importance of understanding arthropod diversity in developing effective pest management strategies for rose cultivation. Additionally, it emphasizes the need for further research on the interactions between pest species and their host plants, which can further refine pest control practices and minimize crop loss.